Concept and Design Developments in School Improvement Research Longitudinal, Multilevel and Mixed Methods and Their Relevance for Educational Accountability - Oude Groote Beverborg, Arnoud; Feldhoff, Tobias; Maag Merki, Katharina; Radisch, Falk (Accountability and Educational Improvement, 2021)
This open access book discusses challenges in school improvement research and different methodological approaches that have the potential to foster school improvement research. Research on school improvement and accountability analysis places high demands on a study's design and method. The potential of combining the depth of case studies with the breath of quantitative measures and analyses in a mixed-methods design seems very promising. Consequently, the focus of the book lies on innovative methodological approaches. The book chapters address design, measurement, and analysis developments as well as theoretical and conceptual developments. The relevance of the research presented in the chapters for educational accountability is discussed in the book's discussion chapter. More specifically, authors present one specific innovative methodological approach and clarify that approach with a concrete example in the context of school improvement, based on empirical data when possible. In this way, this book helps researchers designing complex useful studies.